Effects of lesion size, shape, and resection amount on the final length of the scar in staged excision: An animal experiment in pigs - Jeong, Jinwook; Park, Minwoo; Son, Daegu (Archives of Aesthetic Plastic Surgery, 2020)
Background In staged excision procedures, it is difficult to estimate the number of excisions that will be required and the extent of scar lengthening. The purpose of this study was to investigate the effects of the size, shape, and resection amount of lesions on the outcomes of staged excision through an animal experiment. Methods In total, 20 ellipses with five different designs (n=4) were evaluated on pig skin. The experiment consisted of two groups: group 1 had excisions of the same length, but with different widths, while group 2 had excisions of the same size, but with different amounts of resection. The size of the lesions and the amount of resection were analyzed in terms of the ratio of length (long axis) and width (short axis) (S/L ratio). Results In the first group, initial ellipses measuring 5×4, 5×3, and 5×2 cm increased in size to 9.25±0.07 (185%), 8.55±0.07 (171%), and 8.10±0.14 cm (162%), respectively. In the second group, in which all ellipses measured 5×3 cm, those with a resection amount of 5×1.5, 5×2, and 5×2 cm with a fish fin grew to 8.75±0.15 (175%), 8.55±0.07 (171%), and 8.60±0.17 cm (172%), respectively. In group 1, the larger the S/L ratio, the longer the final length. In group 2, a greater resection amount was associated with a shorter final length. Conclusions We believe that the measurements of this study in terms of shape, size, and excision amount will be reasonable predictive references for staged excision procedures.